Change in Cardiopulmonary Arrest Response in an Anesthesiology Residency: A practice-based learning initiative - Takla, Amgad (J Educ Perioper Med, 2007)
Because of increases in the acuity in our patient population, increasing complexity of the care provided and the structure of our residency, we decided to systematically alter our participation in the hospital-wide cardiac arrest system. The need to provide optimum service in an increasingly complex clinical care system was the motivation for change. With substantive input from trainees and practitioners, we created a multi-tier-system of response along with predefined criteria for the anesthesiology response. We report the result of our practice based learning initiative.